Peningkatan Literasi Keuangan Melalui Edukasi Keuangan Syariah (Pengabdian Masyarakat di Masjid Muhammadiyah Al-Muhajirin) - Akbar, Ilham; Yusuf, Mahmud; Rahman, Abidir; Ilmi, Fajrul; Maghfur, Achmad; DND, PP Rabiah Al Adawiyah; Sannya, Jasmine Ghina; Husna, Khodimatul; Abduh, Muhamad Rahmani (Abdimas Indonesian Journal, 2024)
Financial literacy is the most important indicator in financial management. With good financial literacy, people are believed to be able to manage their finances properly. Conversely, without good financial literacy, people will not have enough provisions to make the right financial decisions and end up with various financial problems. The Sharia Financial Education community service activity carried out at the Muhammadiyah Al-Muhajirin Mosque was carried out as an effort to increase financial knowledge in order to improve the financial literacy of the community. This activity consists of a preliminary stage, main stage, and closing stage. The implementation of the Sharia Financial Education community service activity has gone well and has succeeded in improving the financial literacy of the community. This is evidenced by the increase in the test points of the participants after listening to the material provided and through a series of question and answer sessions.